Association between children's emotional/behavioral problems before adenotonsillectomy and postoperative pain scores at home. Issue 9 (5th August 2018) - Berghmans, Johan M.; Poley, Marten J.; van der Ende, Jan; Veyckemans, Francis; Poels, Stephanie; Weber, Frank; Schmelzer, Bert; Himpe, Dirk; Verhulst, Frank C.; Utens, Elisabeth
Summary: Background: Children undergoing adenotonsillectomy are at risk of severe postoperative pain and sleep problems. Little is known about the specific child risk factors for these problems. Aims: The aim of this study was to assess the occurrence of postoperative pain, sleep problems, and medication adherence, and assess the influence of internalizing and externalizing problems on postoperative pain. Methods: This prospective cohort study included 160 children, aged 1.5‐5 years undergoing day‐care adenotonsillectomy. Parents rated their child's pain with the Parents' Postoperative Pain Measure and their child's sleep problems with Vernon's Post Hospital Behavioral Questionnaire during the first 3 days and at day 10 postoperatively. Emotional/behavioral problems (ie, internalizing and externalizing behaviors) during the past 2 months were assessed using the Child Behavior Checklist. Regression analysis was used to assess whether children's pain intensity at home was associated with internalizing/externalizing problems, after controlling for age, preoperative child state anxiety, parental state anxiety, parental need for information, and socioeconomic status. Results: Applying a threshold of ≥6 on the Parents' Postoperative Pain Measure, the incidence of moderate to severe pain was 57.6% at day 1, 53.5% at day 2, 35.4% at day 3, and 4.8% at day 10. During the first three postoperative nights, 37.1% of the children woke up. Internalizing problems ( β = 0.343; P = 0.001) and parental need for information ( β = 0.207; P = 0.011) were independently associated with higher pain scores at home during the first 3 days ( R 2 = 0.225). Conclusion: Following adenotonsillectomy, children often experienced moderate to severe pain and sleep problems during the first 3 days at home. Preoperative internalizing problems and parental need for information were independently associated with increased pain at home. Screening for these problems can help to identify vulnerable children and adapt the perioperative analgesic strategy accordingly (which includes preparation, information, and prescription of pain analgesics).